A miniaturized mm‐wave leaky wave antenna based on CRLH slow‐wave SIW for symmetric wide angle beam scanning. Issue 10 (18th June 2022) - Agarwal, Ruchi; Das, Sushrut; Yadava, Ram Lal
Abstract: In this article, a novel miniaturized wide beam scanning range multi‐layered mm‐wave leaky‐wave antenna (LWA) based on slow‐wave (SW) substrate‐integrated waveguide (SIW) is presented. The SW effect is introduced by loading conventional SIW with internal metalized blind vias connected to the bottom ground plane. The SW effect in the SIW structure causes the separation of the electric and magnetic field components in the structure which leads to the reduction in lateral dimensions of the proposed topology by 35% as compared to the conventional SIW. The proposed LWA exhibits a miniaturized volume of 6.6 × 0.41 × .07 λ 3 . The radiation in the proposed design is realized by introducing U‐shaped slots in the unit cell of the SW‐SIW structure. Experimental results show that the proposed SW‐SIW LWA achieves almost symmetric and continuous beam scanning from −48° to 52° including the broadside direction within the impedance bandwidth of 23.7–28.1 GHz. The proposed antenna achieves a peak gain of 14.52 dBi and the half‐power beamwidth of LWA is as low as 10°. The proposed antenna also exhibits radiation efficiency of above 90% within the bandwidth. The proposed design can be a potential candidate for mm‐wave frequency beam scanning applications.